Targeted muscle reinnervation and regenerative peripheral nerve interface for the prevention and management of post-amputation pain: A systematic review. - Shunmugavelu, Dr. Karthik; Dhinakaran, Dr. Evangeline Cynthia; Dhatchnamoorthy, Dr . Manigandan (Student’s Journal of Health Research Africa, 2023)
Background Post-amputation pain, including phantom limb pain, residual limb pain, and neuroma-related pain, remains a persistent clinical problem despite advances in surgical care. Physiologic nerve reconstruction techniques such as targeted muscle reinnervation (TMR) and regenerative peripheral nerve interface (RPNI) have been introduced to improve nerve regeneration and reduce neuropathic pain following limb loss. Objective: To evaluate the clinical effectiveness of TMR and RPNI in preventing and treating post-amputation pain. Methods A systematic review was conducted according to PRISMA 2020 guidelines. PubMed/MEDLINE, Scopus, Web of Science, and Google Scholar were searched through January 2026. Eligible studies included peer-reviewed clinical investigations evaluating TMR and/or RPNI in upper- or lower-limb amputees reporting pain-related outcomes. Risk of bias was assessed using ROB-2 and ROBINS-I tools. Results Six studies were included: one randomized clinical trial and five prospective or retrospective studies. In the randomized trial, TMR produced significantly greater reduction in phantom limb pain compared with standard neuroma excision (mean change −3.2 vs −0.2 on a 0–10 scale; p < 0.05). Prophylactic TMR reduced symptomatic phantom limb pain incidence (19% vs 47%; p < 0.05). TMR was also associated with significant improvements in residual limb pain and PROMIS pain interference scores at 12 months (p < 0.05). Prophylactic RPNI reduced symptomatic neuroma formation (0% vs 13%; p < 0.05). Complications were infrequent and predominantly minor. Conclusion TMR and RPNI reduce post-amputation pain, particularly when performed prophylactically. Further research Large multicenter randomized trials with standardized outcome measures are needed to define optimal timing and long-term effectiveness.